The cost of health care for AIDS patients in Saskatchewan - Browne, Kevin P (Pulsus Group Inc, 1990)
The medical records of 19 patients with acquired immune deficiency syndrome (aids) were reviewed in an attempt to estimate their health care costs. The patients were all male, members of high risk groups and diagnosed between April 1985 and February 1988. Twelve of the patients died; they lived a mean of 240 days (range 0 to 580) after diagnosis, were admitted three times (range one to six) to hospital for 65 total days (range one to 148) for a cost per patient of $33,721 (range $2,768 to $64,981) for inpatient care. They made five (range zero to 25) office visits per patient costing $196 per patient (range $0 to $4,999) for outpatient care. The seven survivors (one was lost to follow-up) have lived 375 days (range 186 to 551) since diagnosis, have been admitted to hospital two times (range zero to seven) for 30 total days (range zero to 86) for a total cost per patient of $14,223 (range $0 to $39,410) for inpatient care. They have made 11 office/emergency room visits (range zero to 46) costing in total $4322 (range $0 to $13,605) for outpatient care. The total expenditure was $546,332 ($28,754 per patient), of which total fees to physicians were $37,210 (6.8%), and estimated costs of laboratory tests $117,917 (21.6%), drugs $36,930 (6.7%), and medical imaging $20,794 (3.8%). Patients now deceased cost $416,445 (mean $34,704 per patient), accounting for 76.2% of overall expenditures. The average medical/surgical and drug costs per patient day in hospital were greater for aids patients than for the average medical/surgical patient in the authors’ institution.